Analysis of seismically‐isolated two‐block systems using a multi–rocking‐body dynamic model - Destro Bisol, Giacomo; DeJong, Matthew; Liberatore, Domenico; Sorrentino, Luigi (Computer-aided civil and infrastructure engineering, 2023)
A novel multibody rocking model is developed to investigate the dynamic response of two stacked rigid blocks placed on a linear base isolation device. The model is used to investigate the dynamic response of a realistic statue‐pedestal system subject to pulse‐like ground motions. The analysis shows that, in general, base isolation increases the safety level of the rocking system. However, for large period pulses or small size blocks, the isolator can amplify the ground motion, resulting in a lower minimum overturning acceleration than for the nonisolated system. Further, the amplification or shock spectrum of a linear mass‐dashpot‐spring oscillator, was found to be the reciprocal of the minimum nondimensional overturning acceleration of the investigated rocking system. Novel rocking spectra are obtained by normalizing the frequency of the pulse by the frequency of the isolator. The analysis also demonstrates how the dynamic response of the two stacked blocks is equivalent to that of a single‐block configuration coincident with the whole system assumed monolithic or the upper block alone, whichever is more slender.